Software Project Scope Alignment: An Outcome-Based Approach. - WOOLRIDGE, RICHARD W.; HALE, DAVID P.; HALE, JOANNE E.; SHARPE, R. SHANE (Communications of the ACM, 2009)
The article discusses software development in the context of issues related to project management, examining the role that project scoping plays in the success or failure of software development projects. Project scoping is defined by the authors as an activity that defines a project's boundary through the identification of software elements expected to be delivered and problem domains needs to be met. A 1994 report found that only 16% of IT (Information Technology) projects were successful. Also discussed is the use of outcome-based scoping (OBS) to reduce the chance of scoping-caused project failure.